Optimization of Formula Granule of Lempuyang Gajah (Zingiber zerumbet (L) J.E.Smith) Rhizome Purified Extract as a Larvicide - Tri Murini; Mae Sri Hartati Wahyuningsih; Achmad Fudholi; Tri Baskoro Tunggul Satoto (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Lempuyang gajah rhizome (Zingiber zerumbet (L) Smith is considered potential as larvicidal. A previous study has shown that the purified extract of Z. zerumbet rhizome was toxic against Adese aegypti larvae. The aim of the study it to formulate a purified extract of Z. zerumbet (L) Smith in granule preparations by combining Sodium starch glycolate, PVP K-30 and tween 80. The granule formulation was optimized by the Simplex Lattice Design (SLD) method with using Design expert program 7.1.5. The results showed that the interaction of the three components can increase the flow rate index, the angle of repose, and reduce absorption. The optimum formula obtained was Sodium starch glycolate 2%, PVP K-30 2%, and Tween 80 5%. The analysis of one sample t-test shows that there is no significant difference between the predicted parameter values and the experimental results of the flow rate index and angle of repose, while the absorption response is significantly different. The optimum formula for granules has larvicidal activity with 100% larval death during 12-hour treatment.